Pengaruh Pertumbuhan dan Hasil Tanaman Kailan (Brassica oleraceae Var. Alboglabra) Pada Perlakuan Konsentrasi dan Interval Waktu Pemberian POC Amura Bio: Kata kunci: konsentrasi; interval, kailan; poc - Defina Arda Resta; Hadi, Pramono; Rachmawatie, Srie Juli (innofarm, 2024)
Using liquid organic fertilizer in agriculture can enhance the population of soil organisms and improve the soil's chemical, physical, and biological properties. This research aimed to determine the interaction of Amura Bio liquid organic fertilizer at various concentrations and time intervals on kailan (Brassica oleraceae Var. Alboglabra). The study was conducted from May to July 2024 in Kedunggalar, Ngawi, East Java. The research design employed was a Complete Randomized Block Design (RAKL) with 2 factors and 9 combinations, repeated 3 times. The first factor was the POC concentration with 3 levels: K1 = 20 ml/l, K2 = 40 ml/l, and K3 = 60 ml/l. The second factor was the time interval with 3 levels: I1 = once every 3 days, I2 = once every 5 days, and I3 = once every 7 days. Observed parameters included plant height, leaf width, root length, fresh fruit weight, and dry fruit weight. The results indicated an interaction between concentration and time interval for the administration of Amura Bio POC on the fresh fruit weight parameters. Amura Bio POC at a concentration of 60 ml/l produced the best results for all parameters, and a time interval of every 3 days provided the best results for several parameters.